KEMAMPUAN RISIO KEUANGAN DALAM MEMPREDIKSI LABA - Nur Fadjrih Asyik, Soelistyo (UGM, 2000)
Financial statements users need financial information of companies to analyze their financial condiion and performance. Financial ratios are useful measures for predicting the future earning changes. The study focuses on the usefulness of financial ratios n predicting future earnings.